Movement patterns of players in the Australian Women's Rugby League team during international competition. Issue 3 (March 2020) - Quinn, K.; Newans, T.; Buxton, S.; Thomson, T.; Tyler, R.; Minahan, C.
Abstract: Objectives: To describe the movement patterns of the Australian Women's Rugby League team during international competition. Design: Retrospective observational study. Methods: Global Positioning Systems technology recorded the movements of players from the Australian Women's Rugby League team (n = 31) during seven international rugby league matches. A subgroup of players (n = 18) that played at least 80 min in a match were categorized into three positional groups: forwards (n = 7), backs (n = 7) and halves (n = 4), and analysed for external outputs that were classified into multiple speed zones. Mean speed (m min −1 ) and mean speed when travelling >12 km h −1 (MS12 ; m min −1 ) were calculated for each 10% interval of playing time of both groups to assess changes in match intensity. Results: Total distance travelled was greater in the first half (3332.9 m compared to 3249.0 m), along with distances travelled at speeds >15 km h −1 (p < 0.05), whereas players travelled further at speeds <6 km h −1 in the second half (p = 0.005). Backs travelled further at speeds <6 km h −1 (p = 0.002) and >15 km h −1 (p = 0.007) compared to forwards. Mean speed significantly reduced across the first and second halves (p < 0.05), while MS12 reduced by ∼40% in the first half of the match (i.e. first ∼5 min compared to the last ∼5 min). Conclusion: These results provide coaches with sport-specific activity profiles of female rugby league players that can be used to individualise training prescription. Given that match-intensity deteriorated across the first and second halves, programs may be targeted at improving endurance and supramaximal exercise tolerance in order for female players to withstand high match-demands of international competition.